Safety of re‐challenging adults with acute lymphoblastic leukemia with PEG‐asparaginase‐induced severe hypertriglyceridemia when treated with a pediatric‐inspired regimen - Ibrahim Al Nabhani; Claire Andrews; Jad Sibai; Eshetu Atenafu; Taylor Young; Steven M. Chan; Vikas Gupta; Dawn Maze; Aaron D. Schimmer; Andre C. Schuh; Karen Yee; Hassan Sibai (eJHaem, 2023)
Abstract PEG‐asparaginase is used as a treatment for Philadelphia‐negative acute lymphoblastic leukemia. In pediatric studies, triglycerides (TGs) were affected more by PEG‐asparaginase than by native L‐asparaginase (10.0% vs. 5.5%). We conducted a retrospective study to determine the safety of re‐challenging adult patients with PEG‐asparaginase after experiencing an episode of severe hypertriglyceridemia (>1000 mg/dl or 11.4 mmol/L). The incidence of hypertriglyceridemia associated with PEG‐asparaginase in adult patients was high (67.5%). Therefore, checking TGs at baseline and monitoring levels while receiving PEG‐asparaginase need to be considered and studied in prospective studies. However, in patients with hypertriglyceridemia not complicated by acute pancreatitis, re‐challenging is safe once TG levels normalize.